2014
DOI: 10.1021/jm5002277
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Modulation of γ-Aminobutyric Acid Type A Receptors by Piperine Derivatives

Abstract: Piperine activates TRPV1 (transient receptor potential vanilloid type 1 receptor) receptors and modulates γ-aminobutyric acid type A receptors (GABAAR). We have synthesized a library of 76 piperine analogues and analyzed their effects on GABAAR by means of a two-microelectrode voltage-clamp technique. GABAAR were expressed in Xenopus laevis oocytes. Structure–activity relationships (SARs) were established to identify structural elements essential for efficiency and potency. Efficiency of piperine derivatives w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 59 publications
2
41
0
Order By: Relevance
“…An extension of the reaction time was not attempted in these cases, since the mass balance indicated significant decomposition of the starting materials. First, a set of four bases (NEt 3 , NaHCO 3 , K 2 CO 3 and NaOAc) and four solvents (MeCN, toluene, THF and DMF) were evaluated (entries [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. While toluene and THF did not facilitate coupling in combination with most bases, the best results were obtained with DMF as the solvent (entries 15-18).…”
Section: Resultsmentioning
confidence: 99%
“…An extension of the reaction time was not attempted in these cases, since the mass balance indicated significant decomposition of the starting materials. First, a set of four bases (NEt 3 , NaHCO 3 , K 2 CO 3 and NaOAc) and four solvents (MeCN, toluene, THF and DMF) were evaluated (entries [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. While toluene and THF did not facilitate coupling in combination with most bases, the best results were obtained with DMF as the solvent (entries 15-18).…”
Section: Resultsmentioning
confidence: 99%
“…This major alkaloid from black pepper was just recently also described by Lee et al to inhibit VSMC migration at a concentration of 100 µM [22]. Piperine and congeners are reported to modulate GABA A receptors and to activate transient receptor potential vanilloid type 1 receptors [33,34]. In pharmacokinetic studies performed in Wistar rats, 1 revealed an absolute oral bioavailability of 24 % [35], and is reported to be a potent bioavailability enhancer for drugs by inhibiting CYP3A4 and human P-glycoprotein [36][37][38][39].…”
mentioning
confidence: 76%
“…We have previously reported the synthesis of compounds 14 [41] and 15-25 [33] including procedures in full experimental detail (l " Fig. 5).…”
Section: Synthesis Of Piperine Analogsmentioning
confidence: 99%
“…[19] Investigations carriedout in the small group of Piper capense active ingredients and other synthetic derivatives of piperine led to the conclusion that for sufficient GABA A binding the carbon chain must contain not less than four carbonsa nd at least one double bond, adjacent to the amide group, and the substituent in the amide moiety should be bulky. [91] 9. Regarding the amide moiety,p otency was enhanced by replacing the piperidine with N,N-dibutyl, N,N-diisobutyl, or N,N-bis(trifluoroethyl) groups.…”
Section: Muscle Relaxant Activitymentioning
confidence: 99%
“…[116,117] ChemMedChem 2015, 10,1302 -1325 www.chemmedchem.org cinnamamide moiety corresponds to the hydrophobic spacer, and the propers ize required for inhibitory activity was confirmed by molecular modeling studies. Song et al reported the anti-inflammatory activity of panobinostat (91), which suppressedv ariousp ro-inflammatory cytokines. N-Hydroxycinnamamide derivatives acting as HDAC inhibitors were mostly considered as drug candidates for cancer.…”
Section: H Dac Inhibitorsmentioning
confidence: 99%